Effects of CuO nanoparticles on insecticidal activity and phytotoxicity in conventional and transgenic cotton. (February 2016) - Le Van, Nhan; Ma, Chuanxin; Shang, Jianying; Rui, Yukui; Liu, Shutong; Xing, Baoshan
Abstract: Nanoparticles and transgenic plants are recent scientific developments that require systematic study to understand their potential risks to human health. The effects of CuO nanoparticles (NPs) on Bt-transgenic cotton and conventional cotton are reported here. CuO NPs inhibited the growth, development, nutrient content, and indole-3-acetic acid (IAA) and abscisic acid (ABA) concentrations of transgenic and conventional cotton. Transmission electron microscopy (TEM) images showed CuO NPs aggregated on the epidermis of conventional cotton leaves, whereas it had reached into the cells of transgenic cotton leaves by endocytosis. Most CuO NPs aggregates were found on the root outer epidermis and the rest were located in intercellular spaces of both conventional and Bt-transgenic cottons. CuO NPs enhanced the expression of the exogenous gene encoding of Bt toxin protein in leaves and roots, especially at low CuO NP concentrations, providing an important benefit for Bt cotton insect resistance. Highlights: CuO nanoparticles significantly inhibited the growth and development of both transgenic and conventional cottons. CuO NPs significantly reduced the uptake of nutrients, such as B, Mo, Mn, Mg, Zn and Fe. Low concentration of CuO NPs enhanced the expression of the Bt toxin protein of Bt-transgenic cotton. This is the first report on the effect of nanoparticles on expression of exogenous Bt gene of Bt transgenic crops.